The effect of self-compassion versus mindfulness interventions on autonomic responses to stress in generalized anxiety disorders - Qi, Xuejun; Shen, Yonghui; Che, Xianwei; Wang, Ying; Luo, Xi; Sun, Lijun (Frontiers in Psychiatry, 2025)
ObjectiveAlthough research on psychological interventions in generalized anxiety disorder (GAD) has provided evidence of their effectiveness regarding self-reported outcomes, few studies have examined their psychophysiological effects. Heart rate is emerging as a potential biomarker of efficacy in anxiety disorders. This study aimed to investigate the effects of a self-compassion intervention versus a mindfulness intervention on physiological arousal in response to induced stress.MethodsForty-seven patients with GAD had heart rate data collected during a stress task before and after a 2-week pharmacological treatment (known as treatment as usual, TAU), a self-compassion intervention + TAU or a mindfulness intervention + TAU. They also reported state anxiety, positive affect, and negative affect at pre- and post- intervention before the stress task. ANOVAs were conducted to analyze the effects on electrocardiogram data self-reported measurements.ResultsSelf-compassion intervention uniquely decreased heart rate response to a stressor whereas mindfulness intervention did not. Both treatments decreased state anxiety and negative affect to a stressor, while increased positive affect in this context. We also demonstrated a significant correlation between decreased heart rate response and less negative emotions.ConclusionThe Findings provides novel physiological evidence that self-compassion interventions buffer stress reactivity in individuals with GAD. Attention shall be paid to the limitations in small and unequal sample size and a non-randomized study design.